2009
DOI: 10.1108/13590790910924948
|View full text |Cite
|
Sign up to set email alerts
|

Corporate financial crime: social diagnosis and treatment

Abstract: Purpose -The purpose of this viewpoint paper is to assist in finding solutions for the growing moral and social issues of financial crime plaguing corporations today. Design/methodology/approach -Methodology includes the synthesis of existing theories in economic sociology and criminology to "diagnose" and "treat" the existing flaws in corporate structures that have led to malaise and malfeasance. Theories include differential association, self-control, and control balance, taking into consideration the charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(72 citation statements)
references
References 28 publications
1
71
0
Order By: Relevance
“…Occupational crime is sometimes labeled elite crime. Hansen (2009) argues that the problem with occupational crime is that it is committed within the confines of positions of trust and in organizations, which prohibits surveillance and accountability. Heath (2008) found that the bigger and more severe occupational crime tends to be committed by individuals who are further up the chain of command in the firm.…”
Section: Bookman (2008) Regardsmentioning
confidence: 99%
See 1 more Smart Citation
“…Occupational crime is sometimes labeled elite crime. Hansen (2009) argues that the problem with occupational crime is that it is committed within the confines of positions of trust and in organizations, which prohibits surveillance and accountability. Heath (2008) found that the bigger and more severe occupational crime tends to be committed by individuals who are further up the chain of command in the firm.…”
Section: Bookman (2008) Regardsmentioning
confidence: 99%
“…Except in rare cases of mass fraud such as the Enron scandal, not all the elite within a given organization or industry will commit crime. Hence, although the elite at the top of their profession and corporation differentially associate with people of equal status in their own and other corporations, not all corporate elites commit crimes and behave in an overtly deviant manner (Hansen, 2009). Gross (1978) argued in his classical article on the theory of organizational crime that a considerable number of areas of sociology, studies of crime and delinquency usually have a International Letters of Social and Humanistic Sciences Vol.…”
Section: Crime Theoriesmentioning
confidence: 99%
“…This is likely to be true of the dark side of financial innovation and calls for a wider examination of the context and motivations driving the undesirable consequences. There appears to be no literature that explicitly addresses the motivation question in the context of financial innovation, nevertheless the literature on white collar and financial crime may have some useful lessons (see for instance Hansen, 2009, Nie, 2009, Tibbs et al, 2011. Clearly the main reason for predatory schemes and abuse of financial innovation is personal gain in some way (See Table 1).…”
Section: Unintended Consequences Of Financial Innovationmentioning
confidence: 99%
“…On the more general corporate governance side Nie (2009) finds that firms not involved in securities fraud (versus those that were) tended to have more outsiders on their boards, the management teams had longer tenures and were more likely to own equity in the business. These insights point to corporate governance considerations (see Table 1 and Hansen, 2009) being an important and complementary weapon to regulatory efforts (including punitive sanctions) in the "war" against the dark side of financial innovation.…”
Section: Unintended Consequences Of Financial Innovationmentioning
confidence: 99%
“…If white-collar crime is defined in terms of the offender, it means crime committed by higher class members of society for personal or organizational gain. They are individuals who are wealthy, highly educated, and socially connected, and they are typically employed by and in legitimate organizations (Hansen, 2009). …”
mentioning
confidence: 99%